ROLE OF SYSTEMATIC INFLAMMATION IN THE DEVELOPMENT OF COMORBIDITY IN CASE OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - V. A. Nikitin; L. V. Vаsilievа; E. M. Tolstykh; A. S. Nogovitsynа (Туберкулез и болезни лёгких, 2017)
Often local inflammation develops into systemic one with total inflammatory response of endotheliocytes, plasma and cellular blood factors, connective tissue, and at the final stages it is manifested through microcirculatory disorders in vital organs and tissues. At present two aspects are being investigated related to systemic inflammation in chronic obstructive pulmonary disease (COPD). Firstly, it is the evaluation of inflammatory load through testing the level of inflammation markers in blood. Secondly, now it is generally recognized that a number of typical extrapulmonary disorders and concurrent diseases develops in COPD patients. Regardless of these general pathogenic mechanisms, the one thing is clear: cardiovascular diseases, body weight loss, osteoporosis and a number of other extrapulmonary manifestations of COPD are related to systematic inflammatory response.